THE RELATIONSHIP BETWEEN GOODWILL OBTAINING FROM BUSINESS ACQUISITION AND PROFITABILITY OF LISTED FIRMS IN THE STOCK EXCHANGE OF THAILAND (SET) - พูลเจริญ, ลัคนา; ประเสริฐศรี, วันชัย (RMUTT Global Business and Economics Review, 2015)
The purpose of this study is to investigate relationship between goodwill obtaining from purchase method business and profitability of listed firms in the Stock Exchange of Thailand (SET) under the conceptual study exploring that acquisition of company will result in bettering the organizational performances. The study extends that originating goodwill is paid for expectation of gaining future excess profits or benefits. The study uses secondary data of listed companies in SET during 2007-2009. There are 208 samples excluding financial business and rehabilitating companies. In data analysis, the study uses frequency, percentage, mean, standard deviation. Multiple regression analysis, multivariate multiple regression analysis (MMRA) in order to describe the relationship between goodwill obtaining from purchase method business and profitability. The ratios used for ratio analysis encompass gross profit margin. Operating profit margin, net profit margin, return on investment (ROI), return on equity (ROE), and average of profitability ratios. The results indicate that the goodwill is positively correlated with profitability by measuring the return on equity. In contrast, the goodwill does not have correlation with the gross profit margin, operating profit margin, net profit margin and return on investment. Furthermore, the results from comparison of mean of profitability of listed firms measured by gross profit margin also revealed that seven types of different industries have different profitability.